SARS-CoV-2 infects multiple species of North American deer mice and causes clinical disease in the California mouse - Lewis, Juliette; Zhan, Shijun; Vilander, Allison C.; Fagre, Anna C.; Aboellail, Tawfik A.; Kiaris, Hippokratis; Schountz, Tony (Frontiers in Virology, 2023)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the virus that causes coronavirus disease-19 (COVID-19), emerged in late 2019 in Wuhan, China and its rapid global spread has resulted in millions of deaths. An important public health consideration is the potential for SARS-CoV-2 to establish endemicity in secondary animal reservoirs outside of Asia or acquire adaptations that result in new variants with the ability to evade the immune response and reinfect the human population. Previous work has shown that North American deer mice (Peromyscus maniculatus) are susceptible and can transmit SARS-CoV-2 to naïve conspecifics, indicating its potential to serve as a wildlife reservoir for SARS-CoV-2 in North America. In this study, we report experimental SARS-CoV-2 susceptibility of two additional subspecies of the North American deer mouse and two additional deer mouse species, with infectious virus and viral RNA present in oral swabs and lung tissue of infected deer mice and neutralizing antibodies present at 15 days post-challenge. Moreover, some of one species, the California mouse (P. californicus) developed clinical disease, including one that required humane euthanasia. California mice often develop spontaneous liver disease, which may serve as a comorbidity for SARS-CoV-2 severity. The results of this study suggest broad susceptibility of rodents in the genus Peromyscus and further emphasize the potential of SARS-CoV-2 to infect a wide array of North American rodents.